Information security practices for the Internet of Things, 5G, and next-generation wireless networks - Sahoo, Biswa, 1982-; Yadav, Suman, 1986- (Advances in information security, privacy, and ethics (AISPE) book series., 2022)
"This book highlights research on secure communication of 5G, Internet of Things (IoT) and Next-Generation wireless networks, along with related areas to ensure secure and Internet-compatible IoT systems"--